Effects of Cetylpyridinium Chloride Resistance and Treatment on Fluconazole Activity versus Candida albicans - Edlind, Merritt P. (Antimicrob Agents Chemother, 2005)
Mouthwash antiseptic cetylpyridinium chloride (CPC) has potent activity against Candida albicans; however, two of five azole-resistant strains showed reduced CPC susceptibility. To further examine the potential for cross-resistance, CPC-resistant mutants were selected in vitro and their fluconazole susceptibility was tested. MICs were unchanged, and trailing growth generally decreased. With CPC-fluconazole combinations, both antagonism and synergism were observed, which can be explained, in part, by CDR1-CDR2 multidrug transporter upregulation.